Management of hyperbilirubinemia in near-term newborns according to American Academy of Pediatrics Guidelines: Report of three cases - Naomi Esthemita Dewanto; Rinawati Rohsiswatmo (Indonesian Pediatric Society, 2009)
All neonates have a transient rise inbilirubin levels, and about 30-50% ofinfants become visibly jaundiced.1,2Most jaundice is benign; however,because of the potential brain toxicity of bilirubin,newborn infants must be monitored to identifythose who might develop severe hyperbilirubinemiaand, in rare cases, acute bilirubin encephalopathyor kernicterus. Ten percent of term infantsand 25% of near-term infants have significanthyperbilirubinemia and require phototherapy. 3The American Academy of Pediatrics (AAP)recommends procedures to reduce the incidenceof severe hyperbilirubinemia and bilirubinencephalopathy, and to minimize the risks ofunintended harm such as maternal anxiety,decreased breastfeeding, and unnecessary costsor treatment.4The guidelines provide a framework for theprevention and management of hyperbilirubinemiain newborn infants of 35 weeks or more ofgestational age (term and near-term newborns).This case report details the management of threenewborns of 35 or more gestational age at theSiloam Lippo Cikarang Hospital, Tanggerang, WestJava, Indonesia according to the AAP guidelines.